Radiolabeling of the antibody IgG M75 for epitope of human carbonic anhydrase IX by 61Cu and 64Cu and its biological testing - Čepa, Adam; Ráliš, Jan; Marešová, Lenka; Kleinová, Markéta; Seifert, Daniel; Sieglová, Irena; Král, Vlastimil; Polášek, Miloslav; Paurová, Monika; Lázníček, Milan; Lebeda, Ondřej (Applied radiation and isotopes, 2019)
Human carbonic anhydrase IX is a membrane enzyme that is significantly expressed in some types of cancer cells, while copper radioisotopes offer wide range of diagnostic, therapeutic and theranostic properties. The work was focused on a new approach to the labelling of antibody IgG M75 for epitope human carbonic anhydrase IX with copper radioisotopes 61Cu and 64Cu and its in vivo testing in mice with inoculated colorectal cancer. Monoclonal antibody IgG M75 for epitope human carbonic anhydrase IX was successfully conjugated with copper-specific chelator "phosphinate" and labelled with 61Cu and 64Cu The obtained molecule has considerable potential as a radioimmuno pharmaceutical suitable for imaging of tumours expressing carbonic anhydrase IX by positron emission tomography (PET).
Keywords: Tumour diagnostics; myši nahé; “phosphinate”; Humans; imunoglobulin G; Carbonic Anhydrase IX; buňky HT-29; radioimunodetekce; Antibodies, Monoclonal; Copper Radioisotopes; tkáňová distribuce; HT29 Cells; Mice, Nude; karboanhydrasa IX; lidé; Radioimmunodetection; zvířata; myši; Antigens, Neoplasm; Mice; antigeny nádorové; radioizotopy mědi; imunokonjugáty; kolorektální nádory; Male; monoklonální protilátky; Immunoconjugates; Positron-Emission Tomography; Cu-61; PET; Animals; mužské pohlaví; radiofarmaka; Immunoglobulin G; Carbonic anhydrase IX; pozitronová emisní tomografie; Cu-64; Tissue Distribution; Colorectal Neoplasms; Radiopharmaceuticals